Variations in ribosomal DNA copy numbers in a genome of Trichophyton interdigitale - Iwanaga, Tomoyuki (John Wiley and Sons Inc., 2020)

(untitled) (Mycoses)
BACKGROUND: Ribosomal DNA (rDNA) reportedly has multiple copies in the fungal genome. The internal transcribed spacer (ITS) region in rDNA is useful for investigating relationships between close taxonomic relatives. Thus, ITS has been widely used as a target gene in medical mycology for the detection of pathogenic fungi and identification of fungal species. However, the rDNA copy number in a genome of Trichophyton interdigitale, the pathogen causing dermatophytosis, currently remains unknown. OBJECTIVE: Clarification of the rDNA copy number in a genome of T. interdigitale. METHODS: rDNA copy numbers in 64 clinical isolates of T. interdigitale were examined using quantitative real‐time PCR (qPCR) with the absolute quantitative method targeting TruMDR2, a single‐copy control gene and the ITS region in rDNA. RESULTS: The copy numbers of the rDNA subunit varied among the 64 strains tested, from 24 to 116 copies per genome. The average rDNA copy number ± standard deviation was 59 ± 16. No correlations were observed between the rDNA copy number and colony colour, colony morphology or molecular type of the non‐transcribed spacer region in rDNA. Experiments on rDNA copy numbers obtained from independent colonies of each strain in single‐spore cultures revealed that the copy number was homogeneous within each strain. CONCLUSION: This is the first study to estimate copy numbers of the rDNA subunit in a genome of T. interdigitale. The rDNA copy number of T. interdigitale varied among the strains tested and was homogeneous within each strain.